Retrospective Analysis of the Factors Affecting Recurrence, Survival, and Effect of Hippocampus Radiotherapy Doses on Neurocognitive Functions in Patients Diagnosed with Glioblastoma Multiforme - Sevilcan İnan; Öznur Dönmez Tutanç; Hülya Ertaş; Fatih Aydemir; Burcu Caner; Turgay Toksoy; Pınar Çona (Gazi Medical Journal)
Objective: This study aimed to evaluate radiotherapy (RT) doses, RT effects on neurocognitive functions, and possible factors that may affect recurrence or death in patients with glioblastoma multiforme (GBM). Methods: The data of 21 patients with GBM were retrospectively analyzed. RT treatment plans and doses and hippocampus ipsilateral and contralateral doses were recorded. The Mini-Mental State Examination (MMSE) is used to assess neurocognitive functions. The time of recurrence and death, if any, of the patients was recorded. Factors such as gender, age, patient performance status, tumor size, tumor localization, type of surgery, and time between surgery and RT were analyzed to determine any effect on the risk of recurrence or death. Results: The median planning target volume dose was 59.86 gray (Gy). The maximum ipsilateral hippocampus dose was 51.85 Gy, and the maximum contralateral hippocampus dose was 46.25 Gy. With the MMSE, 3 of 4 patients had cognitive impairment. At the end of follow-up, 16 patients had recurrence and died. The median disease-free survival was 10 months [95% confidence interval (CI): 5.7-14.2], and the median overall survival was 24 months (95% CI: 16.0-31.9). Only poor performance status increased the risk of recurrence (hazard ratio: 4.31, 95% CI: 1.26-14.70, p=0.02). Conclusion: Because hippocampus shielding was not performed, our hippocampus doses were high. Hippocampal-sparing RT is essential for the preservation of neurocognitive functions. The increased risk of recurrence in patients with poor performance status is possibly related to treatment dose reduction, delay, or discontinuation.